Pendekatan Problem Solving berbantuan Komputer dalam Pembelajaran Matematika - Laswadi, Laswadi (Al-Jabar: Jurnal Pendidikan Matematika, 2015)
Creating effective mathematics learning is a complex and continuous undertaking. Using the right approach of learning and utilizing technological developments is an attempt to improve the quality of learning. This paper examines the problem solving learning computer-assisted and how its potential in developing high-order thinking skills of students.